A percepção dos professores e alunos do ensino fundamental acerca da lei nº 9.433/97 em Santiago/RS - Souza, Gessiana Raquel Castro de (2013)
Nowadays, it becomes increasingly complex the need for transformation of our society, the contemporary link interference causes and consequences of social practices related to inadequate care for the ambience, but bring a new element, the "reflexivity". As a society producing risks, are more reflective, in a context characterized by permanent deterioration processes of their ecosystems, involving a set of actors in the school community at all levels, engaging various knowledge systems and their training in a multidisciplinary perspective. Educators have a critical role in the integration of environmental education in day-to-day school educating students for a critical front socioambientalis crises, with the north to changing habits and social practices and the establishment of an environmental citizenship that mobilizes to the issue of Law 9.433/97.A survey was conducted in the municipality of Santiago / RS. And the survey data conducted in the period from March to November of the year 2011, a total of 369 students from the 4th year of elementary school, totaling 26 public schools and 2 private schools, including state and municipal schools in rural areas, and Also, with 33 school teachers from classes and was done through a questionnaire and use the technique of mind mapping. For the GIS, the information generated in AutoCAD application (R14), were transferred to the software CAMPEIRO 7:21 which allowed the creation of layers observed and after school, spatialized. With regard to mental maps showed the students are receptive to the method, showing great willingness to contribute their drawings. Analyzing the responses of the 28 educators, regarding the concept of the Law 9.433/97, it was discovered that 40% of teachers do not know, 20% of respondents knew that failed to conceptualize, and one (M1) mistook Law of Guidelines and Bases of Education (Law No. 9.394/96 LDBEN.), the other answers did not address the concept adequately, thus becoming evident that the largest portion of our research subjects do not know the law. And there is a need for greater involvement by educators and government for the appropriate management and use of water is really effective.